Losing earth : the decade we could have stopped climate change / (Acc. D2117) - Rich, Nathaniel (UK : Picador, 2019)
Losing Earth: A Recent History is a 2019 book written by Nathaniel Rich. The book is about the existence of scientific evidence for global warming for decades while it was politically denied, and the eventual damage that will occur as a result.